Cross-cultural adaptation and validation of the Spanish version of the Cardiopulmonary Resuscitation Motivation Scale (s-CPRMS): a cross sectional study - Mª Carmen Rodríguez-García; Esteban Montoya-Giménez; Helena Martínez-Puertas; José Miguel Garrido-Molina; Alba García-Viola; Verónica V. Márquez-Hernández (BMC, 2024)
Abstract Background Cardiac arrest remains a serious global health issue worldwide which claims for review and improvement. High motivation among resuscitators could lead to high-quality resuscitation and better outcomes. This study aimed to translate and cross-culturally adapt the Cardiopulmonary Resuscitation Motivation Scale into Spanish and assess the psychometric properties of the Spanish version (s-CPRMS). Methods A sample of critical care and acuity-emergency physicians and nurses (N = 352) participated in an observational cross-sectional study structured in 3 phases. Results Face and content validity was confirmed for the s-CPRMS (s-CVI = 0.88). The ordinal alpha was 0.847, ranging from 0.796 to 0.92 for the factors, indicating good reliability and temporal stability (mean ICC = 0.701; p < 0.001). The Exploratory Factor Analysis (EFA) results showed the s-CPRMS was distributed into four factors that explained 58% of the variance with values of the goodness of fit indices indicating an adequate fit for the model extracted in the Confirmatory Factor Analysis (CFA): χ2 (246) = 402.240; p < 0.001, SRMR = 0.086, RMSEA = 0.059, TLI = 0.965, CFI = 0.969, GFI = 0.990. Conclusions The s-CPRMS is a valid and reliable instrument to assess the motivation of resuscitation teams, which might lead to potential effective strategies to resuscitation quality improvement and outcomes.